Sustainable-green hydrogen production through integrating electrolysis, water treatment and solar energy - Afreenuzzaman Badruzzaman; Seckin Karagoz; Fadwa Eljack (Frontiers in Chemical Engineering)
The growing interest in hydrogen as an alternative fuel has stimulated research into methods that enable the global shift to sustainable, green energy. One promising pathway is the production of green hydrogen via electrolysis, particularly when coupled with renewable energy sources like solar power. Integrating a proton exchange membrane (PEM) electrolyzer with solar energy can aid this transition. Using treated sewage effluent, instead of deionized water, can make the process more economical and sustainable. Thus, the objective of this research is to demonstrate that an integrated electrolysis-water treatment-solar energy system can be a viable candidate for producing green hydrogen in a sustainable manner. This study assesses different combinations of water pretreatment (RO and UF) and solar energy input (PV, ST, and PTC), evaluating their techno-economic feasibility, efficiencies, environmental impact, and sustainability. The study shows that CSP scenarios have the highest CAPEX, roughly fourfold that of PV cases and sevenfold that of national grid cases. Using solar energy sources like PV, ST, and PTC results in high material efficiency (94.87%) and environmental efficiency (98.34%), while also reducing CO2 emissions by approximately 88% compared to the national grid. The process’s economic sustainability averages 57%, but it could reach 90% if hydrogen production costs fall to $2.08-$2.27 per kg. The outcome of this study is to provide a green hydrogen production pathway that is technically feasible, environmentally sustainable, and economically viable.